COMPARATIVE ANALYSIS OF BUCKLING CRITERIA FOR ENGINEERING STRUCTURES. MULTI-DEGREE SYSTEM - Stupishin, Leonid Yulianovich; Moshkevich, Marya Leonidovna (Journal of Applied Engineering Science, 2018)
The criteria of the buckling of engineering structures in terms of the systems with lumped parameters are discussed in the article. The examples of setting buckling problems and their solutions using Timoshenko and Bryan criteria’s, and the criterion of the critical levels of energy are given. The analysis of the compared approaches, their strengths and shortcomings in terms of the multi-degree systems are presented.
Keywords: engineering; buckling